Stability of the resistance to Zabrotes subfasciatus conferred by protein arcelin in common beans plants - Barbosa, Flávia Rabelo; Yokoyama, Massaru; Pereira, Pedro Antônio Arraes; Zimmermann, Francisco José Pfeilsticker (Pesquisa Agropecuaria Brasileira, 2000)
Arcelin is a seed protein found in beans which gives resistance to Mexican bean weevil, Zabrotes subfasciatus (Boh., 1833) (Coleoptera: Bruchidae). Compared with the susceptible cultivars Porrillo 70 and Goiano Precoce, the stability of the resistance conferred by two alleles of the protein arcelin was observed in lines Arc1 and Arc4 after raising the insects for four consecutive generations feeding in the same genotype. The experiment was carried out at Embrapa-Centro Nacional de Pesquisa de Arroz e Feijão (CNPAF), at Santo Antônio de Goiás, Goiás State, Brazil, under non-controlled conditions using a randomized complete block design. In the lines containing arcelin reduction in the number of eggs and emerged adults, insects weight and elongation of the egg/adult cycle was observed. The resistance was greater in the line carrying Arc1 allele. The parameters number of eggs and emerged adults, egg/adult cycle, sexual ratio and males weight was not altered on Arc1 genotype, although a progressive increase of the females weight was observed. On the genotype containing Arc4 allele there was a reduction in the egg/adult cycle, although the number of eggs and emerged adults, sexual ratio and males and females weight were not altered.